Potential of chromolaena odorata and indigenous bacterial consortium for oily wastewater treatment - Aweng Eh Rak; Noor Azlina Ibrahim; Marina Bujang (Lifescience Global, 2012)
This study was carried out to investigate the possibility of using Chromolaena odorata as absorbent and to ascertain as to whether indigenous bacteria has the potential to degrade hydrocarbon from oily wastewater and thereby reducing its toxicity and other negative impacts to the environment particularly on aquatic life. The potential of Chromolaena odorata and indigenous bacteria to remove oil from wastewater was evaluated by measuring total suspended solid (TSS) concentration. The result shows that, about 55% of oil substances were absorbed or removed after 4 hours of Chromolaena odorata application with the optimum dosage of 4mg/L. Growth percentage of bacterial consortium and single pure strain on medium containing oily wastewater was studied. It was found that bacterial consortium, the mixture of Bacillus cereus (KA) and Acinetobacter (TB) shows higher growth among other bacterial consortium and single pure cultures and this consortium was used for further analysis. In addition, the results have shown that, bacterial consortium (KA+TB) exhibited high efficiency to remove TSS at the optimum dosage of 1 mg/L. Absorption and biodegradation rate was increased after being treated with Chromolaena odorata and bacterial consortium mixture. The mixture of Chromolaena odorata powder and bacterial consortium in 4:1 ratio was obtained to significantly removed TSS by 75% in 24 hours.